Transformation of Jodang from Tradition Into Politics - Putri, Rizky Trisna; Fauzi, Agus Machfud; Astuti, Ilmi Dewi; Gamayao, Paul Adynn (UIN Sunan Ampel Surabaya, 2025)
This study examines the Jodang tradition in Kenjo Village, Banyuwangi District, focusing on its cultural, social, and political dimensions. The tradition is held throughout the month commemorating the birth of Prophet Muhammad, during which villagers engage in nightly prayer rituals and distribute Jodang to their neighbors. The ritual serves to honor the Prophet through prayer, praise, and mosque decoration, with Jodang later consumed by the participants. This research employs a qualitative approach with an embedded single-case study design, using interviews, observation, and documentation as primary data collection methods. The analysis is framed by Max Weber’s theory of social action, which provides a lens to interpret how religious and cultural practices can intersect with political behavior. Weber’s typology of action, particularly traditional and value-rational actions helps explain the villagers’ motivations, while also revealing how instrumental rationality emerges in political appropriation of the ritual. Data were analyzed thematically to connect empirical findings with theoretical insights. However, the tradition has also taken on political significance. Politicians increasingly participate by sponsoring or distributing Jodang, using the event as a platform to strengthen their public image and maintain constituent support. As such, Jodang has evolved from a purely religious and cultural practice into a political instrument embedded within local community life.